Industrial training at Elektro Serve (M) Sdn Bhd / Iffah Syasya Radhiah Mazlan - Mazlan, Iffah Syasya Radhiah (Universiti Teknologi MARA, Perlis, 2024)
This report's purpose is to provide an assessment and make some strategic observations on my internship company which is Elektro Serve (M) Sdn. Bhd. Using the Strength, Weakness, Opportunity, and Threats (SWOT) analysis and Political, Economic, Social, Technological, Environmental and Legal (PESTEL) analysis, my research tries to analyse how the company develops strategic intent for their business and organisations. The strategic strategy of the firm, including how itintends to make use of its resources and competencies to explore opportunities and overcome risks, is also included in this report.